IMPLEMENTASI MANAJEMEN KEUANGAN DI SMA ISLAM AL KAMAL SARANG - Rosyidah, Siti (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2024)
This research aims to describe and explain the implementation of educational financial management at Al Kamal Sarang Rembang Vocational School. The type and research approach used in this research is descriptive qualitative with data collection through observation, interviews and documentation. Data analysis techniques are carried out through the stages of data collection, data reduction, data presentation, data verification and drawing conclusions. Based on the source of education funds including: Sources of funds obtained from parents/guardians or the community which are determined through meetings of school committee members, and sources from BOS, PIP and UPZ funds, together to prepare a Draft School Revenue and Expenditure Budget (RAPBS) for aligning the needs of schools and communities and managing education. The research results obtained regarding the allocation and realization of educational financial implementation at Al Kamal Sarang Rembang Vocational School have implemented good management, with planning, implementation, control and evaluation, this can be seen in the accountability report and also monitoring from the community which can be accessed directly via payment application.